Major depression, temperament, and social support as psychosocial mechanisms of the intergenerational transmission of parenting styles. (8th December 2022) - Abraham, Eyal; Letkiewicz, Allison M.; Wickramaratne, Priya J.; Bunyan, Maya; van Dijk, Milenna T.; Gameroff, Marc J.; Posner, Jonathan; Talati, Ardesheer; Weissman, Myrna M.
Abstract: In this three-generation longitudinal study of familial depression, we investigated the continuity of parenting styles, and major depressive disorder (MDD), temperament, and social support during childrearing as potential mechanisms. Each generation independently completed the Parental Bonding Instrument (PBI), measuring individuals' experiences of care and overprotection received from parents during childhood. MDD was assessed prospectively, up to 38 years, using the semi-structured Schedule for Affective Disorders and Schizophrenia (SADS). Social support and temperament were assessed using the Social Adjustment Scale – Self-Report (SAS-SR) and Dimensions of Temperament Scales – Revised, respectively. We first assessed transmission of parenting styles in the generation 1 to generation 2 cycle (G1→G2), including 133 G1 and their 229 G2 children (367 pairs), and found continuity of both care and overprotection. G1 MDD accounted for the association between G1→G2 experiences of care, and G1 social support and temperament moderated the transmission of overprotection. The findings were largely similar when examining these psychosocial mechanisms in 111 G2 and their spouses (G2+S) and their 136 children (G3) (a total of 223 pairs). Finally, in a subsample of families with three successive generations (G1→G2→G3), G2 experiences of overprotection accounted for the association between G1→G3 experiences of overprotection. The results of this study highlight the roles of MDD, temperament, and social support in the intergenerational continuity of parenting, which should be considered in interventions to "break the cycle" of poor parenting practices across generations.